An econometric assessment of external debt sustainability indicators in Zambia - Ng'andwe, Mumbi Tenga (Research of GSB, 2018)
Given inadequate domestic resources, as well as political and social pressures for development projects, Zambia will tend to run high budget deficits, and become very dependent on external debt. Thus debt sustainability becomes a major policy goal. This study investigated the significant macroeconomic factors that can influence external debt sustainability. These are GDP growth; Government revenues; exports; public expenditure; interest rate and exchange rate. The study employed simple Ordinary Least Squares (OLS) as well as a Vector Auto Regression (VAR) to capture dynamic relationships. The results revealed that exports and interest rates were positively related to sustainability. Revenues, GDP growth and Exchange rate were inversely related to debt sustainability. The total expenditure to GDP was inversely related to sustainability while current expenditure was positively related to sustainability probably due to prudent use of current expenditure on economic factors that stimulated growth. Capital expenditure was not significant to sustainability which may reflect the poor attention paid to infrastructure development in Zambia. The impulse response of the solvency indicator to revenue, GDP growth and total expenditure/GDP were generally negative over a ten year period. The policy implication is that in order to keep the debt sustainable, the debt resources must be used to maximise GDP growth and enhance public revenue. The impulse responses from exchange rate and interest rates to shocks on the solvency indicator were positive. The impulse response of SI from impulses in exports was negative. These are factors that are not completely in the control of the Government. The policy implication in contracting international debt is that Government should go for the lowest possible interest rate. Government should do its best to develop credible export promotion policies that can directly impact on the SI and also help to stabilize the exchange rate.